Analysis Of Coffee Farmers' Income (Case Study Of Makarti Boga Farmers' Group) Watutau Village, Poso District - Reny Melawati; Andi Herman Jaya; Edhi Taqwa; Santi Yunus; Ika Rafika (ProBisnis : Jurnal Manajemen, 2024)
This research aims to analyze the business income of the Makarti B oga farmer group. The method used in this research describes income obtained by coffee farmers with the approach studies case, with Approach quantitative descriptive. The results of this study show that the Business income of coffee farming groups in the village of Watutau Regency Poso obtained the following conclusions Farmer Coffee, especially the Makartiboga Farmers Group in the town of Watutau, try to minimize the costs that must be incurred to obtain The profit is proven by the total cost value amounting to IDR 79. Two hundred ninety-two thousand eighty-two of the total costs of all respondents. Revenues from the Makartiboga farming business group in Watutau Village are very high compared to the total costs of IDR 310,200,000 from all respondents ' receipts. The results of summarizing all the total costs and business revenues of the Makartiboga farmer group, the researchers obtained the net income from all respondents was IDR 230,907,918